Stem Cell Quiescence versus Senescence: The Key for Healthy Aging - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Aging tissues lose their homeostatic and regenerative capacities, which has been linked to the degeneration of the stem cells such as the tissue-specific stem cells, the stem cell niches, and systemic cues that regulate stem cell activity.CONTENT: The maintenance of tissue homeostatic and regeneration dependent on its tissue-specific stem cells, that —long-lived cells with the ability to self-renew and differentiate into mature cells. Understanding the molecular mechanisms that governs stem cell survival, self-renewal, quiescence, proliferation, and commitment to specific differentiated cell lineages is critical for identifying the drivers and effectors of age-associated stem cell failure. Such understanding will be critical for the development of therapeutic approaches that can decrease, and possibly reverse and repair the age-related degenerative process in aging tissues.SUMMARY: The exact mechanisms and reasons of aging process were not fully elucidated until now. Stem cells is one of the keys for maintaining tissues heath and understanding how stem cell decline with age will give us opportunities to find strategy in increasing somatic stem cells regenerative capacity and delay the aging process.KEYWORDS: adult stem cell, aging, epigenetic, metabolism, quiescence, senescence